THE SIMALUNGUN CUSTOMARY INHERITANCE SYSTEM (CASE STUDY OF RAMBUNG MERAH VILLAGE, SIMALUNGUN REGENCY) - Nasution, Muhammad Iqbal Hanafi; Zikri, Muhammad (AT-TAFAHUM: Journal of Islamic Law, 2025)
This study aims to examine the existence of Simalungun customary inheritance law in Rambung Merah Village within the context of Indonesia’s legal pluralism. The research method used is field research with a qualitative phenomenological and socio-empirical approach, focusing on the meaning, perceptions, and practices of the community regarding the customary inheritance system. The results show that the Simalungun customary inheritance law, which was previously normative and binding, has now transformed to become more flexible and consensus-based. This change is driven by community awareness of justice values, especially gender justice, and the development of religious moderation. The Muslim community in Rambung Merah tends to leave the customary system due to its discriminatory nature against women, instead referring to Islamic inheritance law. Meanwhile, the Christian community still allows customary inheritance if implemented through deliberation among heirs. The discussion indicates that Indonesia’s legal pluralism encourages adaptation and compromise models in applying customary inheritance law, making it relevant and in line with social developments and religious values. Thus, Simalungun customary inheritance law has not disappeared but transformed into a conditional alternative that prioritizes substantive justice and family harmony in a multicultural society..